Reproductive biology of the ascidians Styela rustica and Halocynthia pyriformis from Kongsfjorden, Svalbard, Arctic - Ferrero, Luciana Andrea; Servetto, Natalia; Laudien, Jürgen; Sahade, Ricardo Jose (Polar Biology)
Ascidians are abundant and well-represented members of worldwide benthic communities, including Antarctica and the Arctic. These organisms exhibit different reproductive patterns usually related to a latitudinal gradient, as do many marine invertebrate species. Reproductive seasonality varies from one or two annual peaks in cold and temperate water species to continuous reproduction throughout the year in warm water species. Styela rustica (Linnaeus 1767) and Halocynthia pyriformis (Rathke 1806) are solitary species with external fertilization and a wide distribution range, from the North Atlantic to the Arctic. The reproductive patterns of these two species were assessed for Arctic populations by year-round sampling and structural analysis of the gonads. Both species are hermaphrodites and showed marked seasonality in oocyte maturity and spawning; S. rustica peaked during the boreal summer and H. pyriformis in late spring. The two species also showed marked differences in mature oocyte sizes: H. pyriformis almost doubled those of S. rustica and, while spermatocytes of H. pyriformis were mature year-round, the maturity of male and female gametes was synchronized in S. rustica. The species thus showed an annual reproductive cycle coupled with a higher production period in the ecosystem, but also exhibited different strategies developed under the same environmental pressures Fil: Ferrero, Luciana Andrea. Universidad Nacional de Córdoba. Facultad de Cs.exactas Fisicas y Naturales. Departamento de Diversidad Biologica y Ecologica. Cat.de Ecologia Marina; Argentina Fil: Servetto, Natalia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto de Diversidad y Ecología Animal. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Instituto de Diversidad y Ecología Animal; Argentina Fil: Laudien, Jürgen. Alfred Wegener Institute; Alemania Fil: Sahade, Ricardo Jose. Consejo Nacional de Investigaciones Científicas y ...